Women's Participation as Tourism Workers is A Form of Recognition of Gender Equality in The Implementation of Patriarchal Culture in Bali - Adnyani, Ni Ketut Sari; Purnamawati, I Gusti Ayu (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2024)
By Decree MUDP X/2010 which legitimizes women to be involved and play an active role like men in the public and domestic spheres. Socio-legal research, data in the form of legal documents, and the results of in-depth interviews are then analyzed using various approaches (legal, theoretical, and historical approaches) using inductive-deductive methods. The research results show that Bali Provincial Regulation 5 of 2020 accommodates the role of Indigenous communities, including Indigenous women, in managing Balinese cultural tourism, therefore Law Number 10 of 2009 is the only reference in managing Balinese cultural tourism. Meanwhile, for Balinese traditional communities, it is known that participation is not only regulated in Bali Provincial Regulation Number 4 of 2019 concerning traditional villages and awig-awig but also in unwritten forms such as pararem pemahcah awig and perarem, ngele. The existence of Indigenous women as public sector workers, namely in tourist villages, is not only found in actual texts, but in general, they live their lives based on customary law which contains applicable values, principles, and norms. Therefore, it is necessary to formulate tourism policies that accommodate the rights of women indigenous workers in the substance of more specific customary law as a source of gender responsiveness. The implication of this study is that Balinese women play a very important role in efforts to maintain family economic resilience. They become solutions to family economic problems through activities such as receptionists, waitresses, gardeners, housekeepers, bartenders and kitchens, and tour guides to meet the family's economic needs. Activities in the public sphere are carried out without leaving their obligations in the domestic sphere. This condition makes Balinese women play a dual role, namely as tourism workers and housewives, which actually supports women to be able to play a dual role.